Registration of 'Dagmar' hard red spring wheat. Issue 1 (17th February 2020) - Heo, H.‐Y.; Lanning, S. P.; Lamb, P. F.; Nash, D.; Wichman, D. M.; Eberly, J.; Carr, P.; Kephart, K. D.; Stougaard, R. N.; Torrion, J.; Miller, J.; Chen, C.; et al.
Abstract: 'Dagmar' hard red spring wheat ( Triticum aestivum L.) (Reg. no. CV‐1158, PI 690450) was released by the Montana Agricultural Experiment Station because of its excellent yield potential in dryland areas of Montana, solid stems, and superior end‐use quality. Dagmar was a selection from the cross MT1133/MT1148 and was tested as experimental line MT1621. Dagmar has similar grain yield potential to 'Vida', the most widely grown cultivar in Montana. Stems of Dagmar are more solid than those of Vida, suggesting increased resistance to the wheat stem sawfly ( Cephus cinctus Norton). Dagmar has higher grain protein and stronger gluten than Vida. Thus, Dagmar should be useful in Montana and adjoining states facing drought and wheat stem sawfly pressure.